2008
DOI: 10.4321/s0213-61632008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the elderly community: II. Outcome in a 4.5 years follow-up

Abstract: -Background and Objectives:In this study, we test to what extent negative outcomes of depression reported in different countries may be confirmed in a Southern European population.Methods: This is a follow-up (mean 4.5 years) of the elderly sample interviewed in the baseline of the Zaragoza Study (or ZARADEMP 0). The general methodology is described in the previous paper. The same two-phase procedure completed at baseline was also implemented at follow-up and the same standardized instruments were used. Cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
1
0
2
Order By: Relevance
“…It has been shown that the direction of this association seems to run from multimorbidity to depression 4,5 . As individuals age, they tend to become alone, losing friends and family members, which renders them susceptible to depressive symptoms 6 . Furthermore, with age they are subject to brain vascular injury due to hypertension, diabetes mellitus, obesity, and high blood cholesterol 7 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the direction of this association seems to run from multimorbidity to depression 4,5 . As individuals age, they tend to become alone, losing friends and family members, which renders them susceptible to depressive symptoms 6 . Furthermore, with age they are subject to brain vascular injury due to hypertension, diabetes mellitus, obesity, and high blood cholesterol 7 .…”
Section: Introductionmentioning
confidence: 99%
“…O número de sintomas depressivos não foi significativamente maior nos diferentes grupos etários avaliados, seja em RP ou CS, o que corrobora com os achados de Morais (2007) num estudo com idosos longevos no RS. Entretanto, outros autores verificaram que a idade está positivamente associada a um aumento de sintomas depressivos entre idosos em geral, tanto em estudos nacionais (GAZALLE et al, 2004;CASTRO-COSTA et al, 2008), quanto internacionais (WEYERER et al, 2008;CAMARA et al, 2008).…”
Section: Depressãounclassified
“…Os autores verificaram ainda que houve uma associação significativa entre depressão e baixo nível educacional, ser viúvo ou morar sozinho. Camara et al (2008) avaliaram os desfechos negativos da depressão num estudo de coorte com idosos espanhóis (idade média = 78 anos) e evidenciaram que 70% dos casos de depressão, seja leve ou severa, evoluíram para a morte, cronicidade ou conversão para outros diagnósticos psiquiátricos, contra 31% dos não casos.…”
Section: Depressãounclassified